Preliminary Observation of Biogas Production from a Mixture of Cattle Manure and Bagasse Residue in Different Composition Variations - H Hadiyanto; Figa Muhammad Octafalahanda; Jihan Nabila; Andono Kusuma Jati; Marcelinus Christwardana; Kusmiyati Kusmiyati; Adian Khoironi (International Journal of Renewable Energy Development, 2023)
The need of renewable energy is paramount important as it is expected to replace fossil energy. One of renewable energy commonly used for rural area is biomass-based energy. Biogas is a biomass-based energy where organic materials are converted to methane gas via anaerobic digestion process. The limitations of mono-feedstock biogas are instability digestion process, low yield biogas produced and require readjusting C/N ratio, therefore co-digestion process was proposed to overcome these problems. This study aims to investigate the feasibility of anaerobic co-digestion of a mixture of cattle manure and bagasse residue in different weight ratio combinations. Biogas was generated by anaerobic digestion using a mixed substrate composed of a combination of weight ratios of bagasse:cattle manure (1:5, 1:2, 1:1, and 3:1). The kinetic analysis was evaluated by fitting Gompertz and Logistic model to experimental data of cumulative biogas. The result showed that the combination of 1:5 ratio of bagasse waste to cattle manure obtained the best biogas yield with cumulative biogas at 31,000 mL. The kinetic model of Gompertz and Logistic were able to predict the maximum cumulative biogas at ratio of 1:5 (cattle: bagasse) at 31,157.66 mL and 30,112.12 mL, respectively. The other predictions of kinetic parameters were maximum biogas production rate (Rm)= 1,720.45 mL/day and 1,652.31 mL/day for Gompertz and Logistic model, respectively. Lag periods were obtained at 2.403 day and 2.612 day for Gompertz and Logistic model, respectively. The potential power generation of 338.71 Watt has been estimated from biogas. This research has proven a positive feasibility of co-digestion of two feed-stocks (cattle manure and bagasse) for biogas production.